Teleintervention for users of augmentative and alternative communication devices: A systematic review. (31st August 2022) - Bekteshi, Saranda; Konings, Marco; Karlsson, Petra; Criekinge, Tamaya Van; Dan, Bernard; Monbaliu, Elegast
Abstract : Aim: To synthesize existing evidence on the effectiveness of speech‐language teleinterventions delivered via videoconferencing to users of augmentative and alternative communication (AAC) devices. Method: A systematic literature search was conducted in 10 electronic databases, from inception until August 2021. Included were speech‐language teleinterventions delivered by researchers and/or clinicians via videoconferencing to users of AAC devices, without restrictions on chronological age and clinical diagnosis. The quality of the studies included in the review was appraised using the Downs and Black checklist and the Single‐Case Experimental Design Scale; risk of bias was assessed using the Risk Of Bias In Non‐Randomized Studies ‐ of Interventions and the single‐case design risk of bias tools. Results: Six teleinterventions including 25 participants with a variety of conditions, such as Down syndrome, autism, Rett syndrome, and amyotrophic lateral sclerosis met the inclusion criteria. Five studies used a single‐case experimental design and one was a cohort study. Teleinterventions included active consultation ( n  = 2), functional communication training ( n  = 2), brain–computer interface ( n  = 1), and both teleintervention and in‐person intervention ( n  = 1). All teleinterventions reported an increase in participants' independent use of AAC devices during the training sessions compared to baseline, as well as an overall high satisfaction and treatment acceptability. Interpretation: Speech‐language teleinterventions for users of AAC devices show great potential for a successful method of service delivery. Future telehealth studies with larger sample sizes and more robust methodology are strongly encouraged to allow the generalization of results across different populations. What this paper adds: Individuals can learn to use augmentative and alternative communication (AAC) devices independently during tele‐AAC interventions. Service providers and recipients reported an overall high satisfaction and acceptability for AAC services delivered via teleinterventions. Speech‐language teleinterventions may be an effective method of providing AAC intervention services. What this paper adds: Individuals can learn to use augmentative and alternative communication (AAC) devices independently during tele‐AAC interventions. Service providers and recipients reported an overall high satisfaction and acceptability for AAC services delivered via teleinterventions. Speech‐language teleinterventions may be an effective method of providing AAC intervention services.